Expression and significance of miR-30d-5p and SOCS1 in patients with recurrent implantation failure during implantation window - Yuhao Zhao; Dongmei He; Hong Zeng; Jiefeng Luo; Shuang Yang; Jingjing Chen; Raed K. Abdullah; Nenghui Liu (BMC, 2021)
Abstract Background Poor endometrial receptivity is a major factor that leads to recurrent implantation failure. However, the traditional method cannot accurately evaluate endometrial receptivity. Various studies have indicated that microRNAs (miRNAs) are involved in multiple processes of embryo implantation, but the role of miRNAs in endometrial receptivity in patients with recurrent implantation failure (RIF) remains elusive. In the present study, we investigated the presence of pinopodes and the roles of miR-30d-5p, suppressor of cytokine signalling 1 (SOCS1) and the leukaemia inhibitory factor (LIF) pathway in women with a history of RIF during the implantation window. Methods Endometrial tissue samples were collected between January 2018 to June 2019 from two groups of women who underwent in vitro fertilisation and embryo transfer (IVF-ET) or frozen ET. The RIF group included 20 women who underwent ≥ 3 ETs, including a total of ≥ 4 good-quality embryos, without pregnancy, whereas the control group included 10 women who had given birth at least once in the past year. An endometrial biopsy was performed during the implantation window (LH + 7). The development of pinopodes in the endometrial biopsy samples from all groups was evaluated using scanning electron microscopy (SEM). Quantitative reverse transcription-polymerase chain reaction and western blotting were used to investigate the expression levels of miR-30d-5p, SOCS1, and the LIF pathway. Results The presence of developed pinopodes decreased in patients with RIF on LH + 7. The expression level of miR-30d-5p decreased in the endometria during the implantation window of patients with RIF, whereas the mRNA and protein levels of SOCS1 were significantly higher in the RIF group than in the control group. Furthermore, a negative correlation was observed between the expression of miR-30d-5p and SOCS1 (r 2 = 0.8362). In addition, a significant decrease in LIF and p-STAT3 expression was observed during the implantation window in patients with RIF. Conclusions MiR-30d-5p and SOCS1 may be potential biomarkers for endometrial receptivity. Changes in pinopode development and abnormal expression of miR-30d-5p, SOCS1 and LIF pathway in the endometrium could be the reasons for implantation failure.